Tingkat Kesejahteraan Keluarga Nelayan pada Masa Pandemi Covid-19 di Kelompok Nelayan “Astitining Segara” Kelurahan Sanur, Kecamatan Denpasar Selatan - MBARAANTI, ANGGRANI MARTAN; DEWI, RATNA KOMALA; DARMAWAN, DWI PUTRA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
The Level of Welfare of Fishermen's Families during the covid-19 pandemic in the Fishermen's Group "Astitining Segara" in Sanur Village, South Denpasar Subdistrict.  Fishermen as a group that has role is important in development, especially in the fisheries sector. This is considering its direct involvement in the utilization of fishery resources. The purpose of this study is to analyze (1) the level of welfare of the fishing family (2) the income of the fishermen's family and (3) the constraints and efforts of fishermen. This research was conducted on the fishing group "Astitining Segara" in Sanur Village, South Denpasar Subdistrict. A sample of 33 members with saturated sampling method of the fishing group was analyzed quantitatively and qualitatively. The results showed that the level of welfare of fishermen's families in the fishing group "Astitining Segara according to the criteria is 63,63% of fishing families classified into prosperous families and 36,36% of fishing families classified into families that are not prosperous. the income of fishing families derived from fishing (on fishing) Rp 2.704.769,00/month with a percentage of  95,16% of the income of traditional fishing families, and the income of  traditional  fishermen outside the fisheries sector (non fishing) was only Rp137.500,00/month with a percentage of  4,83%. The obstacles faced by fishermen are the lack of capital in purchasing fishing gear and weather. Efforts to meet capital to buy fishing gear are asking the Denpasar City Government for help, while fishermen's efforts to deal with weather instability usually wait in good condition. Fishermen are advised to borrow capital from cooperatives or village banks to purchase the fishing gear needed in the following periods.